EVALUATION OF ANTIESTROGEN DRUG AND STEM ENHANCE IN AMELIORATION OF HISTOPATHOLOGICAL EFFECTS OF BISPHENOL A ON VITAL ORGANS IN MURINE MODEL: HISTOLOGICAL AND IMMUNOHISTOCHEMICAL STUDIES - AHMED S ALAZZOUNI; BASMA N HASSAN (International Journal of Pharma and Bio Sciences, 2016)
BisphenolA found in plastic vessels used for children feeding is an endocrine disrupting compound. It is a contaminant with increasing exposure to it and exerts both toxic and estrogenic effects on mammalian cells. There for this study was designated to evaluate the histopathological and immunohistochemical an effect of BPA on histoarchtecture of vital organs of albino rats and the ameliorative effect of antiestrogen drug and stem enhance on histopathological and immunohistochemical changes of these tissues (liver, kidney and pancreas) . Experiment model : 20 albino rats weighing 100 – 120 gm. were kept under observation for about 15 days before the onset of the experiment for adaptation, then the rats were classified into 4 groups 5 rats for each , the first group was left without any treatment for 30 days as negative control group, the second group was administered with 20 mg/kg.bw/ day of BPA for 15 consecutive days as positive control, the third group administered with 20 mg/kg.bw/ day of BPA for 15 consecutive days and then treated with (0.1 mg/ 100gm.bw/day antiestrogen drug for 15 day, the fourth group administered with the same dose of BPA for the same period and then treated with 4.5 mg/100.bw/day stem enhance for 15 days, all rats are scarified and organs were histologically examined after processing pancreas